Extent of D2 Surgery for Colon Cancer According to Tumor Location with Respect to Vascular Anatomy and Lymph Node Metastasis - Takahashi, Toshio; Takenaka, Atsushi; Sawai, Kiyoshi; Ohara, Miyakatsu; Takahashi, Shigeru; Taniguchi, Hiroki; Yada, Hirokazu; Shimotsuma, Masataka; Tokuda, Hajime; Katoh, Makoto; Izumi, Hiroshi; Ikawa, Osamu (The Japanese Journal of Gastroenterological Surgery, 1996)
In order to determine the extent of D2 surgery for colon cancer in each location, we reviewed the angiograms of 344 colon cancer patients and lymph node metastasis of 63 colon cancer patients with n2 metastasis. Our findings were summarized as follows: Since the ileocecal artery always branched from the supeiror mesenteric artery and n2 metastasis of cecum cancer was limited to No.202, D2 surgery for cecum cancer can be carried out using ileocecal resection. As the right colic artery had variant origins and ascending colon cancer had n2 metastasis in various n2 stations, D2 surgery for ascending colon cancer requires right hemicolectomy. The middle colic artery forked into the right and left branches and each branch had different branching variations. When the right colic artery and the middle colic artery has a common trunk, D2 surgery for D2 surgery for transverse colon cancer on the right side should be performed usin right hemicolectomy. When the left branch of the middle colic artery has an independent replaced origin, lymph node dissection should be modified according to the variant origin. When the left colic artery and the first sigmoidal artery have a common trunk, lymph node dissection should include No.242-1 for descending colon cancer and No.232 for sigmoid colon cancer respectively. D2 surgery for sigmoid colon cancer should include dissection of No.252, because 39% of sigmoid colon cancer with 2 metastases showed metastasis of that station.